Differential Expression Pattern of THBS1 and THBS2 in Lung Cancer: Clinical Outcome and a Systematic-Analysis of Microarray Databases. - Tzu-Yang Weng; Chih-Yang Wang; Yu-Hsuan Hung; Wei-Ching Chen; Yi-Ling Chen; Ming-Derg Lai (PLoS ONE, 2016)
Thrombospondin 1 and thrombospondin 2 (THBS1 and THBS2) share similar multifunctional domains, and are known to be antiangiogenic. However, the expression pattern of THBS1 and THBS2 is different, and the specific role of THBS2 in different subtypes of lung cancer remains largely unclear. To evaluate the significance of THBS1 and THBS2 in the development of lung cancer, the present study performed a microarray-based systematic-analysis to determine the transcript levels of thrombospondins and their relation to the prognosis in lung cancer. THBS1 was in general underexpressed in lung cancer; in contrast, mRNA levels of THBS2 were markedly overexpressed in a number of datasets of non-small cell lung carcinoma (NSCLC), including lung adenocarcinoma (AC) and squamous cell carcinoma. Similar expression pattern of THBS1 and THBS2 was verified in pulmonary AC cell lines with real-time PCR analysis. The survival of lung AC patients with high THBS2 mRNA expression levels was poorer than patients with low levels of expression of THBS2. In a microarray-based analysis, genes coexpressed with THBS1 or THBS2 were determined. Pulmonary AC patients with a high expression level of sevenTSHB1-coexpressed genes (CCL5, CDH11, FYB, GZMK, LA-DQA1, PDE4DIP, and SELL) had better survival rates than those with a low expression level. Patients with a high expression of seven TSHB2-coexpressed genes (CHI3L1, COL5A2, COL11A1, FAP, MXRA5, THY1, and VCAN) had poor survival rates. Downregulation of VCAN and THBS2 with shRNA inhibited the cell proliferation in the A549 cell line. In summary, THBS1 functions as a tumor suppressor in lung adenocarcinoma. However, THBS2 may play a double-edged role in the progression of lung AC, i.e. anti-angiogenic and oncogenic function. Further study on the mechanism underlying the activity of THBS2 is warranted to have further implications for cancer diagnosis and treatment of pulmonary AC.